Aggregation Pheromones and Host Kairomones of West Indian Sugarcane Weevil, Metamasius hemipterus sericeus - Campos, Y. (1997)
Coupled gas chromatographic–electroantennographic detection (GC-EAD) analyses and coupled GC-mass spectrometry (MS) of volatiles produced by male and female West Indian sugarcane weevils (WISW), Metamasius hemipterus sericeus (Oliv.), revealed eight male specific, EAD-active compounds: 3-pentanol (1), 2-methyl-4-heptanol (2), 2-methyl-4-octanol (3), 4-methyl-5-nonanol (4), and the corresponding ketones. In field experiments in Florida, alcohols 1–4 in combination with sugarcane were most attractive, whereas addition of the ketones or replacement of alcohols with ketones significantly reduced attraction. In Costa Rica field experiments testing alcohols 1–4 singly and in all binary, ternary, and quaternary combinations revealed 4 in combination with 2 was the major aggregation pheromone, equally attracting male and female WISW. Stereoisomeric 4 and (4S,5S)-4, the only isomer produced by WISW, were equally attractive. Addition of 4S-, 4R- or (±)-2 to (4S,5S)-4 significantly enhanced attraction. Sugarcane stalks in combination with 2 plus 4 (ratio of 1:8) were highly synergistic, whereas EAD-active sugarcane volatiles ethyl acetate, ethyl propionate, or ethyl butyrate only moderately increased attractiveness of the pheromone lure.